The Influence of Block Chain-Enabled Supply Chain Systems on Transaction Transparency in Multinational Corporations in Canada - Thompson , Michael (International Journal of Computing and Engineering, 2025)
Purpose: The purpose of this article was to influence of block chain-enabled supply chain systems on transaction transparency in multinational corporations in Canada. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: ​ Blockchain-enabled supply chain systems have improved transaction transparency in Canadian multinationals by providing secure, real-time records that reduce errors and fraud. Companies report better traceability and trust, though high costs and technical challenges still limit wider adoption. Overall, blockchain has a strong positive impact on supply chain transparency. Unique Contribution to Theory, Practice and Policy: Transaction cost theory (TCT), resource-based view (RBV) & technology-organization-environment (TOE) may be used to anchor future studies on the influence of block chain-enabled supply chain systems on transaction transparency in multinational corporations in Canada. Mental health support is not just a wellness initiative it is a strategic retention tool. At the policy level, this study supports the integration of mental health standards into labor and occupational health regulations within the healthcare sector.